Digital Transformation: Digitising Witness Statements in South African Policing in Alignment with Religious Principles - Nomsa Ingrid Zikalala; Jacob Tseko Mofokeng; Moses Morero Motseki; Enoch Zenzile (Khazanah Journal of Religion and Technology, 2024)
The utilisation of new technologies towards supporting effective and accountable policing is increasingly dependent on e-government development and other technological advancements. England and Wales have long moved from paper witness statements to digitally recorded statements, known as Digital Witness Statements (DWS). DWS refers to the digital capture, representation, and storage of the information needed for its use as an evidential witness statement in courts in England and Wales. This paper presents a prototype system that could be employed in the South African policing context, aligning with religious principles to ensure cultural sensitivity and ethical considerations.  The aim of this study was to create awareness that digitisation has been an efficient method of capturing witness statements in the European policing context. Additionally, this study aimed to highlight the status quo of taking indigenous witness statements in South Africa. The objective was to explore the phenomenon of taking indigenous witness statements and to establish the South African Police Service (SAPS) members’ perceptions of the current methods. The study also examined how incorporating religious principles can enhance the acceptance and effectiveness of these digital methods within diverse communities.  Thematic content analysis was conducted using Atlas.ti, and measures of trustworthiness were applied. Three dominant themes—“skills,” “resources,” and “duration”—emerged. The Theory of Performance (ToP) was used, and results indicated that SAPS members identified resources as a barrier to their performance. Integrating religious principles into the digitisation process may address some cultural barriers, fostering a more inclusive and respectful approach to modernising witness statement collection.